TECHNIQUE OF VIVNNYA І VODOSKONALENNYA TEKHNIKI STOCK VOLLEYBALL - Гейченко C.; Скидан I.; Коротя B.; Оргєєва C. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with main development trends of volleyball. This kind of sport evolves velocity, attention, agility, hardworking, endurance as well as raises filling of collectivism, discipline and responsibility. Identified the most effective methods of technical and tactical training of volleyball players that have been tested in practice. The main methodological problems are the choice of the best ways to study, fix and improve the technique of playing volleyball, in the correct use of methods, means and principles that guarantee the greatest training effect. The technique of the game is the rational use of the whole set of techniques and methods that volleyball players use during the game. On the basis of the conducted research the dynamics of development of motor abilities in the age aspect, the role of anatomical and physiological parameters, the parameters of various phases of the attacking impact were studied, the zones of the volleyball court were analyzed in which the attacking blow of reactions of different age groups is used often. The optimal method of solving problems and selecting the means and methods of training is offered. Mastering of the physical training is the core training, because in this case physical movement acts as an object, a means, and a goal of improvement. The purpose of this study was to develop a methodology of physical movement training in volleyball using the fundamentals of the education activity theory and developmental training and to test the methodology’s effectiveness in experimental work. In the experimental group, the fist training sessions showed a slight decrease in the physical density of the training sessions. This occurred because more time was spent on theoretical conversations, discussion of issues of interest, development of the training model and its use to test the main parts of the physical movements under study. The main conditions of game are accurate transmission, blocking, strike attack, tactics and technique of players. All these aspects will have a positive impact on the cognitive interest of students, will contribute to the formation of the morals and spirituality of youth, their comprehensive harmonious development and will help to master the technique and practice of the game, thus laying the foundation that ensures the achievement of athletic skill знання з даного питання. Обґрунтовано, що на різних етапах тренування волейболістів, поряд із фізичними якостями, техніко-тактична підготовка є однією з основних. Також виявлено, що тактика, як і техніка гри розділяють на тактику нападу і тактику захисту які були перевірені на практиці. Основними умовами гри є точна передача, блокування, атака страйку, тактика і техніка гравців. Всі ці аспекти матимуть позитивний вплив на пізнавальний інтерес студентів, сприятимуть формуванню моралі та духовності молоді, їх всебічному гармонійному розвитку і допоможуть освоїти техніку і практику гри, закладаючи основу забезпечує досягнення спортивної майстерності